Instant Karma (Fortuna Beach, ,, 2020)
In New York Times bestselling author Marissa Meyer's young adult contemporary romance, a girl is suddenly gifted with the ability to cast instant karma on those around her – both good and bad. Chronic overachiever Prudence Barnett is always quick to cast judgment on the lazy, rude, and arrogant residents of her coastal town. Her dreams of karmic justice are fulfilled when, after a night out with her friends, she wakes up with the sudden ability to cast instant karma on those around her. Pru giddily makes use of the power, punishing everyone from public vandals to mean gossips, but there is one person on whom her powers consistently backfire: Quint Erickson, her slacker of a lab partner. Quint is annoyingly cute and impressively noble, especially when it comes to his work with the rescue center for local sea animals. When Pru resigns herself to working at the rescue center for extra credit, she begins to uncover truths about baby otters, environmental upheaval, and romantic crossed signals—not necessarily in that order. Her newfound karmic insights reveal how thin the line is between virtue and vanity, generosity and greed . . . love and hate... and fate.

With a little luck (Fortuna Beach, ,, 2024)
After being magically given incredible luck, sixteen-year-old Jude discovers this gift just may be a curse when it comes to love.